Six new epigean species of the genus Falcileptoneta Komatsu, 1970 (Araneae: Leptonetidae) from South Korea - Oh, Jong-Hwa; Lee, Seunghwan (Zootaxa, 2023)
Six new leptonetid species belonging to Falcileptoneta Komatsu, 1970 are described from South Korea: F. alboclavata sp. nov., F. decemspina sp. nov., F. innuta sp. nov., F. jindoensis sp. nov., F. stilla sp. nov., and F. triformis sp. nov. All newly described species were sampled from epigean habitats (e.g. leaf litter or under the stone). Based on both male and female (except F. jindoensis sp. nov.), diagnostic characteristics, microscopic images of adult specimens and reproductive structures, and distribution records are provided. Additionally, morphological details to diagnose Falcileptoneta is also discussed.